2018
DOI: 10.1021/acsomega.8b02461
|View full text |Cite
|
Sign up to set email alerts
|

SAPO-34/5A Zeolite Bead Catalysts for Furan Production from Xylose and Glucose

Abstract: SAPO-34 zeolite crystals were grown on zeolite 5A beads, characterized, and then used to produce furfural from xylose and 5-hydroxymethylfurfural (HMF) from glucose. The SAPO-34/5A bead catalysts resulted in moderate furfural and HMF yields of 45% from xylose and 20% from glucose (463 K; 3 h) and were easier to recover than the SAPO-34 powder catalyst. At 463 K, the SAPO-34/5A beads were more selective than 0.02 M sulfuric acid for producing HMF and, unlike the sulfuric acid system, no levulinic acid was forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Despite the fact that application to nanoporous systems is challenging, due to the small structural length dimensions which generate complex rotational and translational molecular dynamics over a hierarchy of scales, significant characterization of systems such as zeolites has been attained [ 3 , 4 , 5 , 6 ]. The application of zeolites in catalytic conversion of biomass to fuel and chemical products is an area of growing application [ 7 ], and recent research has shown that zeolite beads have the potential to catalyze sugar to furan dehydration reactions [ 8 ]. Studies of water molecular dynamics in zeolites in the presence of biomolecules by NMR have been limited to solid state NMR spectroscopy, PGSE NMR using a single displacement observation time [ 9 ], and PGSE NMR to study water in zeolites [ 10 , 11 ] while solid state NMR has also been used to study solvents in zeolites [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the fact that application to nanoporous systems is challenging, due to the small structural length dimensions which generate complex rotational and translational molecular dynamics over a hierarchy of scales, significant characterization of systems such as zeolites has been attained [ 3 , 4 , 5 , 6 ]. The application of zeolites in catalytic conversion of biomass to fuel and chemical products is an area of growing application [ 7 ], and recent research has shown that zeolite beads have the potential to catalyze sugar to furan dehydration reactions [ 8 ]. Studies of water molecular dynamics in zeolites in the presence of biomolecules by NMR have been limited to solid state NMR spectroscopy, PGSE NMR using a single displacement observation time [ 9 ], and PGSE NMR to study water in zeolites [ 10 , 11 ] while solid state NMR has also been used to study solvents in zeolites [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of water molecular dynamics in zeolites in the presence of biomolecules by NMR have been limited to solid state NMR spectroscopy, PGSE NMR using a single displacement observation time [ 9 ], and PGSE NMR to study water in zeolites [ 10 , 11 ] while solid state NMR has also been used to study solvents in zeolites [ 12 ]. Here displacement time-dependent PGSE NMR was applied to study the impact of xylose on water dynamics in zeolites for heterogeneous catalysis of sugars to furans [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolite molecular sieve 5A is a type of calcium ion exchange and synthetic bubble-zeolite, which possesses a larger specic surface area and more uniform aperture compared to a natural zeolite. [24][25][26][27] It is oen used as a gas adsorbent and catalyst support. (3-Aminopropyl)triethoxysilane (APTES) is a silane coupling agent with amino groups, which has been showing a good capacity towards the adsorption of Cr(VI) ions.…”
Section: Introductionmentioning
confidence: 99%